(untitled) (The Pretoria Student Law Review, 2021)
This article examines the ideal epistemic aims of a critical jurisprudence in South Africa. It explains that epistemology is concerned with giving an account of knowledge and suggests that if legal scholars ought to aim at having their students acquire knowledge then their epistemic aims should be related to this goal. I contend that the epistemic aims of the law do not necessarily concern curricular subjects but with the way the work of a legal scholar should be guided by an understanding of the nature of knowledge itself. This paper not only deals with the historical development of political traditions but also gives attention to religious and communal intellectual practices. This paper also mulls the development of a South African critical race theory with reference to the thought of Steve Biko. In a wide sense, the purpose of this paper is also to bring the insights of the Black Radical Tradition to bear on the study of law and jurisprudence, with attention placed on the predicament of ‘post’-apartheid South Africa. In essence, this paper demonstrates that: ‘Only by rethinking the ideas that made us can we re-imagine the world’.